Pelanggaran Persaingan Usaha dan Problematika Eksekusi Atas Putusan KPPU - Arifin Ma’ruf (UIN Sunan Kalijaga Yogyakarta, 2016)
The genesis of Law No. 5 of 1999 on Prohibition Monopili and UnfairBusiness Competition is expected to be a solution to the problem of unfair businesscompetition that had been rife in Indonesia, the Commission dirikanya spirit in orderto